Gut Microbiota Dysbiosis Induced by Intracerebral Hemorrhage Aggravates Neuroinflammation in Mice - Yu, Xiaobo; Zhou, Guoyang; Shao, Bo; Zhou, Hang; Xu, Chaoran; Yan, Feng; Wang, Lin; Chen, Gao; Li, Jianru; Fu, Xiongjie (Frontiers in Microbiology, 2021)
Intracerebral hemorrhage (ICH) induces a strong hematoma-related neuroinflammatory reaction and alters peripheral immune homeostasis. Recent research has found that gut microbiota plays a role in neurodegeneration and autoimmune diseases by regulating immune homeostasis and neuroinflammation. Therefore, we investigated the relationship between ICH, microbiota alteration, and immune responses after hematoma-induced acute brain injury. In our study, we used a mouse model of ICH, and 16S ribosomal RNA sequencing showed that ICH causes gut microbiota dysbiosis, which in turn affects ICH outcome through immune-mediated mechanisms. There was prominent reduced species diversity and microbiota overgrowth in the dysbiosis induced by ICH, which may reduce intestinal motility and increase gut permeability. In addition, recolonizing ICH mice with a normal health microbiota ameliorates functional deficits and neuroinflammation after ICH. Meanwhile, cell-tracking studies have demonstrated the migration of intestinal lymphocytes to the brain after ICH. In addition, therapeutic transplantation of fecal microbiota improves intestinal barrier damage. These results support the conclusion that the gut microbiome is a target of ICH-induced systemic alteration and is considered to have a substantial impact on ICH outcome.